Phytoplankton Response to Saharan Dust Depositions in the Eastern Mediterranean Sea: A Mesocosm Study - Lagaria, Anna; Mandalakis, Manolis; Mara, Paraskevi; Papageorgiou, Nafsika; Pitta, Paraskevi; Tsiola, Anastasia; Kagiorgi, Margarita; Psarra, Stella (Frontiers in Marine Science, 2017)
The response of phytoplankton populations from surface ultra-oligotrophic waters of the Eastern Mediterranean Sea to Saharan dust additions was studied during a 10-day mesocosm experiment in May 2014. A set of triplicate mesocosms entitled ‘Single Addition’ treatment (SA) was amended with Saharan dust once, while another triplicate set entitled ‘Repetitive Addition’ treatment (RA) received the same amount of dust divided into three consecutive daily doses administered within the first three experimental days, both simulating patterns of dust deposition events taking place in the field. In both treatments, dust particles released small amounts of dissolved inorganic nitrogen and phosphorus which stimulated by two-fold both chlorophyll-a concentration and primary production for a time period of six days, as compared to a set of control mesocosms carried out without dust addition. Phytoplankton response was similar in both treatments, regardless of the dust addition pattern, and it evolved through two distinct phases in both cases. The first phase (i.e. 1 to 2 days after initial addition) was characterized by enhancement of picoplankton chlorophyll-normalized production rates as a result of elevated orthophosphate concentrations while the second phase (i.e. 3 to 4 days after initial dust addition), was characterized by elevated chlorophyll-normalized production rates corresponding to larger cells (> 5 μm) as a result of increased mineral nitrogen concentrations. The stimulated primary production of larger cells was not accompanied by a respective increase in carbon biomass suggesting important top-down control. The major phytoplankton taxa detected during the experiment were Synechococcus, Pelagophytes and Prymnesiophytes. Estimations of cellular pigment concentrations and carbon-to-chlorophyll ratios of identified groups and differences between prokaryotic and eukaryotic cells are discussed.